Laser Microperforation Assisted Drug-Elution from Biodegradable Films - Arkady S. Abdurashitov; Pavel I. Proshin; Olga A. Sindeeva; Gleb B. Sukhorukov (MDPI AG, 2022)
In a modern high-tech medicine, drug-eluting polymer coatings are actively used to solve a wide range of problems, including the prevention of post-surgery infection, inflammatory, restenosis, thrombosis and many other implant-associated complications. For major assumptions, the drug elution mechanism is considered mainly to be driven by the degradation of the polymer matrix. This process is very environmentally dependent, unpredictable and often leads to a non-linear drug release kinetic. In the present work, we demonstrate how the laser microperforation of cargo-loaded biodegradable films could be used as a tool to achieve zero-order release kinetics with different elution rates. The effects of the laser-induced hole's diameter (10, 18, 22, 24 µm) and their density (0, 1, 2, 4 per sample) on release kinetic are studied. The linear dynamics of elution was measured for all perforation densities. Release rates were estimated to be 0.018 ± 0.01 µg/day, 0.211 ± 0.08 µg/day, 0.681 ± 0.1 µg/day and 1.19 ± 0.12 µg/day for groups with 0, 1, 2, 4 microperforations, respectively. The role of biodegradation of the polymer matrix is reduced only to the decomposition of the film over time with no major influence on elution rates.